The Natural Compound Oblongifolin C Exhibits Anticancer Activity by Inhibiting HSPA8 and Cathepsin B In Vitro - Han, Li; Xu, Danqing; Xi, Zhichao; Wu, Man; Nik Nabil, Wan Najbah; Zhang, Juan; Sui, Hua; Fu, Wenwei; Zhou, Hua; Lao, Yuanzhi; Xu, Gang; Guo, Cheng; et al. (Frontiers in Pharmacology, 2020)
PPAPs (Polycyclic polyprenylated acylphloroglucinols) are a class of compounds with diverse bioactivities, such as anticancer effects. Oblongifolin C (OC) is a PPAP isolated from the plant of Garcinia yunnanensis Hu. We previously discovered that OC induces apoptosis, inhibits autophagic flux, and attenuates metastasis in cancer cells. However, the protein targets and detailed mechanism of action of OC remain unclear. To identify protein targets of OC, a non-labeled protein fishing assay was performed and found that OC interacts with several proteins, including the heat shock 70kDa protein 8 (HSPA8). Expanding our previous studies on protein cathepsin B, this study confirmed the interaction between OC and two protein targets through multiple chemical biology techniques, including Surface Plasmon Resonance (SPR), Isothermal Titration Calorimetry (ITC) etc. This study highlights the inhibitory effect of OC on HSPA8 in cancer cells under heat shock stress, by specifically inhibiting the translocation of HSPA8. OC also enhanced the interaction between HSPA8, HSP90 and p53, upregulated the expression of p53 and significantly promoted apoptosis in cisplatin-treated cells. Additionally, flow cytometry assay detected that OC sped the apoptosis rate in HSPA8 knockdown A549 cells, while overexpression of HSPA8 delayed the OC-induced apoptosis rate. In summary, our results revealed that OC interacts with HSPA8 and cathepsin B, inhibits HSPA8 nuclear translocation and cathepsin B activities, altogether suggesting the potential of OC to be developed as an anticancer drug.